Regional Integration of the Association of Southeast Asian Nations Economic Community: An Analysis of Malaysia - Association of Southeast Asian Nations Exports - Zainal Abidin, Irwan Shah; Haseeb, Muhammad; Islam, Rabiul (International Journal of Economics and Financial Issues, 2016)
Malaysia is a rapid growing economy especially in the Association of Southeast Asian Nations (ASEAN) region. The exports with ASEAN countries plays vital role in economic growth and development of Malaysia. Additionally, current chairmanship of ASEAN makes Malaysia more prominent in the region. Consequently, exploring the determinants of Malaysia – ASEAN-5 countries, namely Singapore, Thailand, Indonesia, Philippine and Vietnam exports performance is a fundamental objective of this study. The panel data of Malaysia and other ASEAN-5 countries for the period 1990 – 2013 and renowned international trade model ‘Gravity' has been applied to explore the determinants. The results of the study explore that distance, population size, economic size and exchange rate are the significant potential determinants of Malaysia – ASEAN exports during the period of study. The findings of this study provide lucid and wide range policies for Malaysian government to boost the economic growth and development through exports promotion with ASEAN countries. Keywords: Malaysia, ASEAN, AEC, Gravity, Exports JEL Classifications: F13, F4, P45